Characterization of hepatitis B virus DNA integration patterns in intrahepatic cholangiocarcinoma. Issue 1 (6th November 2020) - Li, Mengge; Du, Min; Cong, Hui; Gu, Yuanyuan; Fang, Yuan; Li, Jin; Gan, Yu; Tu, Hong; Gu, Jinyang; Xia, Qiang
Abstract : Aim: Hepatitis B virus (HBV) integration is one of the mechanisms contributing to hepatocellular carcinoma (HCC) development. However, the status of HBV integration in intrahepatic cholangiocarcinoma (ICC) is poorly understood. This study aims to characterize the viral integration in HBV‐related ICC. Methods: The presence of HBV S and C gene in ICCs and the paratumor tissue was determined by polymerase chain reaction direct sequencing. Hepatitis B virus integration was detected by a high‐throughput capture sequencing method. The expression analysis of the genes targeted by HBV in ICC was undertaken in The Cancer Genome Atlas dataset. Results: Hepatitis B virus S and/or C gene fragments were detected in 71.43% (10/14) ICCs and 57.14% (8/14) paratumor tissues. Using the high‐throughput capture sequencing approach, 139 and 183 HBV integration breakpoints were identified from seven ICC and seven paired paratumor tissues, respectively. Seven genes ( TERT, CEACAM20, SPATA18, TRERF1, ZNF23, LINC01449, and LINC00486 ) were recurrently targeted by HBV‐DNA in different ICC tissues or different cell populations of the same tissue. TERT, which is the most preferential HBV target gene in HCC, was found to be repeatedly interrupted by HBV‐DNA in three different ICC tissues. Based on The Cancer Genome Atlas dataset, TERT, as well as three other HBV recurrently targeted genes ( SPATA18, TRERF1, and ZNF23 ), showed differential expression levels between ICC and para‐ICC tissues. Conclusions: Taken together, HBV integration is a common event in HBV‐related ICC. The HBV recurrent integration genes identified from this study, such as TERT, provide new clues for further research on the causative link between HBV infection and ICC.